Adolescent Perspectives in Eastern Indonesia on Social Motivation in Alcohol Consumption: A Qualitative Study - Violin Irene Ninef; Otniel Blegur; Leviana Surya (Jurnal Vocational Nursing Sciences (VNUS), 2022)
Introduction: Alcohol consumption among teenagers is a significant public health issue on a global scale. However, the levels of alcohol consumption among teenagers and their understanding of its impact on human health are still relatively poorly documented in various regions of Indonesia, especially among teenagers in the eastern regions of Indonesia. Objective: This research aims to comprehend the social motivations driving alcohol consumption among teenagers in Eastern Indonesia, identify contributing motivations, and investigate their implications in clinical nursing practice. Method: This study employs a qualitative approach with a descriptive design. The study population consists of teenagers aged 16–17 in the eastern region of Indonesia. Sampling was conducted using the snowball sampling method based on predefined inclusion criteria. The data were gathered through in-depth interviews, recorded using audio recording devices, and supplemented with field notes. Data analysis was carried out using the Colaizzi method, continuing until data saturation was achieved. Result: The research findings reveal a variety of perspectives among East Indonesian teenagers regarding alcohol consumption, including cultural normalization of drinking and youth parties, factors associated with adolescent alcohol consumption, conflicting feelings about alcohol consumption, and alcohol consumption as a symbol of masculinity. Conclusion: This study underscores the importance of a more holistic approach to understanding and addressing alcohol consumption issues among teenagers in Eastern Indonesia. Clinical nursing practice implications involve intensifying health education efforts for adolescents and developing more effective interventions to reduce the risks associated with alcohol consumption among teenagers, particularly in Eastern Indonesia